Ischemia in Anomalous Aortic Origin of a Right Coronary Artery: Large Pediatric Cohort Medium-Term Outcomes. (18th April 2023) - Doan, Tam T.; Sachdeva, Shagun; Bonilla-Ramirez, Carlos; Reaves-O'Neal, Dana L.; Masand, Prakash; Mery, Carlos M.; Binsalamah, Ziyad; Heinle, Jeffrey H.; Molossi, Silvana
Abstract : Background: Anomalous aortic origin of a right coronary artery may cause myocardial ischemia and sudden death in the young. Data on myocardial ischemia or longitudinal outcomes are sparse in pediatric anomalous aortic origin of a right coronary artery population. Methods: Patients <21 years with anomalous aortic origin of a right coronary artery were prospectively enrolled. Computerized tomography angiography defined morphology. Exercise stress test and stress perfusion imaging (sPI) were performed if >7 years or younger with concern for ischemia. High-risk features included intramural length, slit-like/hypoplastic ostium, exertional symptoms, or evidence of ischemia. Results: A total of 220 patients (60% males) were enrolled December 2012 to April 2020 at a median age 11.4 years (interquartile range, 6.1–14.5), including 168 (76%) with no/nonexertional symptoms (group 1) and 52 (24%) with exertional chest pain/syncope (group 2). Computerized tomography angiography was available in 189/220 (86%), exercise stress test in 164/220 (75%), and sPI in 169/220 (77%). Exercise stress test was positive in 2/164 (1.2%) patients in group 1, both had positive sPI. Inducible ischemia (sPI) was detected in 11/120 (9%) in group 1 and 9/49 (18%) in group 2 ( P =0.09). Intramural length was similar in patients with/without ischemia (5 [interquartile range, 4–7] versus 5 [interquartile range, 4–7] mm; P =0.65). Surgery was recommended in 56/220 (26%) patients with high-risk features. In 52 surgical patients (38 unroofing, 14 reimplantation), all subjects were alive and have returned to exercise at last median follow-up of 4.6 (interquartile range, 2.3–6.5) years. Conclusions: Anomalous aortic origin of a right coronary artery patients can present with inducible ischemia on sPI despite symptoms or intramural length. Exercise stress test is a poor predictor of ischemia and caution should be given to determine low-risk based solely on this assessment. All patients are alive at medium-term follow-up.